ANALISIS ORIENTASI PASAR, MODAL SOSIAL DAN INOVASI PRODUK TERHADAP KINERJA PEMASARAN PEDAGANG DI PUSAT GROSIR SOLO - Reny Dwi Astuti; Bambang Mursito; Rochmi Widayanti (ITB AAS INDONESIA Surakarta, 2019)
This research is k a test of the influence of marketk orientation, social capital and product innovation lon marketing performance at Pusat Grosir Solo. The populationkin this studylis traders in Pusat Grosir Solo, the sample of the research amounted to 100 people, sampling techniques using accidental sampling, which is done by givingpa questionnairepto be filled out by traders at Pusat Grosir Solo. The data analysiss method used inn this study is descriptivepstatistical analysisoand regressionpanalysis. Descriptiveo statistical analysisiis thekinterpretation of datakobtained in the studypand the results of data aprocessing that has been carried out by giving explanations and explanations. Regression analysis includes validityy and reliabilityk test, classic assumptionm test, mmultiple regressionn analysiss, determination test, F test and t ttest. The results of the F test show that market orientation, social capital, and product innovation concurrent influence on the marketing performance at the Pusat Grosir Solo. Based on the results of partial hypothesis testing market orientationn has a positivee and significantt effect on marketing performance at the Pusat Grosir Solo. Social capital has a positive and significant effect on marketing performance at the Pusat Grosir Solo. Product innovation has a positive and significant effect on marketing performance at the Pusat Grosir Solo. The results of the coefficient of determination, the results of the calculation of multiplee linearr regressione analysis cann bee seenn that thee adjusted amount of R2 obtained is 0.651 or 65.1%. This shows that market orientation, social capital and product innovation has an influence on the marketing performance of traders at Pusat Grosir Solo by 65.1%. Keyword: Market Orientation, Social Capital, Product Innovation, Marketing Perfomance